A review on the mechanical properties of bio waste particulate reinforced polymer composites. (2021) - Sujin Jose, A.; Athijayamani, A.; Jani, S.P.
Abstract: The growing ecological awareness throughout the world has activated a standard change towards designing better performance materials well-matched to the surroundings. Bio waste particulates like coconut shell, coir pith, groundnut shell, and cashew nut shell, etc., have a great potential as reinforcement in polymer resin matrix (thermosetting and thermoplastic). These bio waste particulates have many advantages such as low cost, low weight, high toughness and hardness, good thermal properties, lower pollution, and biodegradability over conventional reinforcing particulates. The properties of bio waste particulates reinforced polymer composites vary with geometry of particles as well as particulate's structure. However, numbers of drawbacks of bio waste particulate reinforced polymer composites were higher moisture absorption tendency, lower impact strength, and inferior fire resistance. In this review paper, a comprehensive review about the properties of natural bio waste particulates used as potential reinforcing agent in polymer composites is presented. Research works reported on mechanical behaviours of particulate reinforced polymer composites are presented.